2022
DOI: 10.1038/s41598-022-18768-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of cold atmospheric plasma as seedborne fungal disinfectant and promoting mediator for physico-chemical characteristics of Moringa oleifera seedlings

Abstract: Non-thermal atmospheric pressure plasmas are a powerful tool to impact seed germination and microbial decontamination. Air large volume atmospheric pressure glow discharge plasma was developed and investigated to improve the biological activities of Moringa oleifera seeds. Ninty ns magnetic pulse compression high voltage system was used to generate the plasma. The plasma discharges current increases with increasing applied voltage and it decreases with increasing discharge gap. There was a steady reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The plant parts (leaves, fruits, seeds, roots, bark and flowers) have a variety of therapeutic and nutritional benefits in humans. It has been demonstrated that bioactive compounds in the plant leaves, fruits and seeds contain variety of active constituents that have a wide spectrum of biological impacts and pharmacological uses (Nesamani & Plants, 1999;Jacques et al, 2020;Ouf et al, 2022). Numerous studies have identified M. oleifera oil as a potent anti-inflammatory drug (Ezeamuzle et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The plant parts (leaves, fruits, seeds, roots, bark and flowers) have a variety of therapeutic and nutritional benefits in humans. It has been demonstrated that bioactive compounds in the plant leaves, fruits and seeds contain variety of active constituents that have a wide spectrum of biological impacts and pharmacological uses (Nesamani & Plants, 1999;Jacques et al, 2020;Ouf et al, 2022). Numerous studies have identified M. oleifera oil as a potent anti-inflammatory drug (Ezeamuzle et al, 1996).…”
Section: Introductionmentioning
confidence: 99%